ANALYSIS OF CHANGES IN LAND SURFACE TEMPERATURE IN THE OIL AND GAS MINING INDUSTRY SECTOR IN BOJONEGORO REGENCY - Mrabawani insan rendra; Anindya Putri Tamara (Jurnal Sains Informasi Geografi, 2020)
This study aims at determining changes in the surface temperature of the mining and oil and gas mining industry. The method that used was the analysis using the 1997 Land 5 Tm Image and the 2018 Oil Landsat 8 Image and seeing the growth in the GRDP of Bojonegoro Regency. The results of this study show: The surface temperature in Bojonegoro Regency in 1997 an average of 20-30 ° C and 30-35 ° C was in the eastern part of Bojonegoro Regency, namely part of Kanor District, part of Baoureno District, part of Kepohbaru District, part of Sumberejo District, part of Kepohbaru District and part of Sokosewu District. However, there was an increase in soil surface temperature in 2018 in Bojonegoro Regency. At a temperature of 20-30 ° C on the outskirts of Bojonegoro Regency, the average surface temperature of 30-35 ° C is found in almost all of Bojonegoro Regency, and a surface temperature of> 35 ° C is the highest in the Oil and Gas Mining and Mining Industrial Zone located in Gayam District, Bojonegoro Regency